Implementation of the Independent Learning-Independent Campus Program at Cahaya Prima Bone University - Haedar Akib; Andi Fitiah; Isgunandar Isgunandar (Journal of Social Science and Economics (JOSSE), 2025)
This study seeks to assess the execution of the Independent Learning-Independent Campus (MBKM) program at Universitas Cahaya Prima (UNCAPI) Bone and to identify the facilitating and obstructive elements affecting its implementation at UNCAPI Bone. The research employs qualitative methods, utilizing data collection approaches such as observation, interviews, and documentation. This study involved seven informants. The findings of this study indicate that the execution of the MBKM program at UNCAPI Bone, assessed through the indicators of communication, resources, disposition, and bureaucratic structure, has been conducted "effectively." From a communication perspective, there is effective interaction between professors and students. From a resource perspective, lecturers as facilitators offer guidance, support, and inspiration to students. The lecturers exhibit a supportive disposition and maintain a favorable outlook on the execution of the MBKM program. Lecturers have elucidated the mechanisms, systems, and procedures of the MBKM program to students from a bureaucratic structural perspective. The facilitating elements for the execution of the MBKM program include the endorsement from universities, the favorable outlook of lecturers, and the proactive engagement of students in the MBKM initiative. Concurrently, the impediments include inadequate value conversion, insufficient socialization, disorganized human resource development, and a continued lack of student enthusiasm in the MBKM program.